Chorioamnionitis, lung function and bronchopulmonary dysplasia in prematurely born infants. Issue 4 (20th November 2010) - Prendergast, Michael; May, Caroline; Broughton, Simon; Pollina, Elena; Milner, Anthony D; Rafferty, Gerrard F; Greenough, Anne
Abstract : Objective: To determine whether prematurely born infants exposed to chorioamnionitis compared to those not exposed have poorer lung function and are more likely to develop severe bronchopulmonary dysplasia (BPD). Design: Results were analysed from consecutive infants born at <33 weeks gestation with placental histology results and lung function measurement results on days 2 and/or 7 after birth and/or at 36 weeks postmenstrual age (PMA). Setting: Tertiary neonatal intensive care unit. Patients: 120 infants with a median gestational age of 29 (range 23–32) weeks were studied, 76 (63%) developed BPD and 41 (34%) had been exposed to chorioamnionitis and/or funisitis. Interventions: Chorioamnionitis was diagnosed histologically. Main outcome measures: Lung function was assessed by measurement of lung volume and compliance and resistance of the respiratory system. If the infants remained oxygen dependent beyond 28 days, they were diagnosed at 36 weeks PMA to have mild BPD (no longer oxygen dependent), moderate BPD (required less than 30% oxygen) or severe BPD (required more than 30% oxygen and/or positive pressure support). Results: No significant differences were found in the lung function results between the chorioamnionitis and non-chorioamnionitis groups at any postnatal age. There was no significant relationship between chorioamnionitis and the occurrence or severity of BPD. Regression analysis demonstrated BPD was significantly related only to birth weight, gestational age and use of surfactant. Conclusion: In prematurely born infants, routinely exposed to antenatal steroids and postnatal surfactant, chorioamnionitis was not associated with worse lung function or more severe BPD.